Peanut Cultivar Differences in Yield Based on Source and Sink Characteristics - Iskandar Lubis; Heni Purnamawati; Roedhy Poerwanto; , Yudiwanti; Ahmad Ghozi Mansyuri; Sri Astuti Rais (Indonesian Journal of Agronomy, 2012)
This research was conducted to determine peanut cultivar differences in sink and source sizes as represented by vegetative growth and yields. Two sets of experiments were conducted at Bogor Agricultural University farms, Sawah Baru and Cikarawang (06o33’, S, 106o45’E, 250 m altitude). Planting was conducted on June 12 and June 20, 2007 using 20 local and national cultivars in each location. Both experiments used randomized complete block design with three replications. Data were analyzed using correlation and regression analysis. Size of experimental unit was 1.6 m x 4.0 m, with planting density 125,000 plants ha-1. Urea, SP36 and KCl were applied at planting date in the rate of (kg ha-1) 45 N, 100 P2O5 and 50 K2O. Four stages of plant growth were studied: 25 days after planting (DAP); 6 weeks after planting (WAP); 10 WAP (pod filling) and 14 WAP (harvest). Five plants were sampled at 25 DAP, two plants at 6 WAP, 10 WAP and 14 WAP, and separated into leaves, stems, roots and pods. The average yield of two experimental stations showed that Biawak cultivar had the highest yield due to relatively higher aboveground dry weight (source), pod filling percentage and maximum number of gynophor+pods (potential sink). Jepara cultivar had the lowest yield due to low pod filling percentage and potential sink, although its source was considered to be in the medium category. Above ground dry weight at 6 and 10 WAP had close relation with Crop Growth Rate (CGR) during 25 DAP-6 WAP and 6-10 WAP, and the higher CGR during those periods were more related to leaf area index than to single leaf photosynthetic capacity. Keywords: crop growth rate, pod filling percentage, leaf area index, single leaf photosynthetic capacity